Sexual Abuse, Post-Traumatic Stress Disorder and Psychopathological Characteristics in Women with Functional/Dissociative Seizures - Lanzillotti, Alejandra Inés (2024)
Background: Functional/dissociative seizures (FDS), also known as psychogenic non-epileptic seizures (PNES), are sudden, transient, and involuntary events that include motor, sensory, cognitive or autonomic function alterations. In this work we analyzed the psychopathological characteristics of a subgroup of women who suffer from FDS with the aim to analyze the role of psychological trauma, with special emphasis on trauma due to sexual abuse (SA). Methods: Forty-five women diagnosed with FDS were included in the study (age range 18 to 64 years, Mean = 34.7, standard deviation (SD) = 13.1). Clinical and psychopathological characteristics were reviewed. All patients have completed the clinical interviews, the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I), the Structured Clinical Interview for DSM-IV Axis II Personality Disorders (SCID II) and the Global Assessment of Functioning (GAF) according to a special protocol for mental health assessment. Also, the history of sexual abuse trauma, the history of other non-sexual traumas and absence of history of trauma were reviewed. Results: Eighty percent of the cases reported a history of trauma, and 40% reported a history of SA. Patients with a history of SA presented a significantly lower average age of seizure onset than patients with a history of other non-sexual traumas (p = 0.021). Significant associations were found between SA and post-traumatic stress disorder (PTSD) (p = 0.031), and SA and history of suicide attempts (p = 0.037). Conclusions: SA carries serious implications for the mental health of women suffering from FDS. Mental health professionals must consider the history of this type of trauma to provide the necessary care for this patient population.